Hemolysis and hypersensitive tests ease culture collection management of antagonistic bacteria - Amaria, Widi; Meity Suradji Sinaga; Kikin Hamzah Mutaqin; Supriadi; Widodo (Universitas Lampung, 2023)
A biosafety assessment is a crucial first step in the management of microbial culture collection to screen and determine unexpected potential plant and human pathogenic bacteria. It is common to collect and store as many fresh culture collections from natural resources before being further evaluated for antagonist bacteria. As a result, a bulk of isolates must be preserved which required more effort and budget. Safety evaluations based on the hemolysis and hypersensitive reactions offer simple tests to ease culture collection management of antagonist bacteria. The study aimed to evaluate the safety of bacterial culture collection for their hemolysis and hypersensitive reactions. Ninety-five isolates of rhizosphere and endophytic bacterial isolates from the culture collections of the Department of Plant Protection-IPB University, Indonesian Industrial and Beverages Crops Research Institute, and Indonesian Spice and Medicinal Crops Research Institute, were evaluated their safety using the hemolysis and hypersensitive tests. The hemolysis test was conducted using blood agar media, from which isolates with a negative (?) reaction were then tested for the hypersensitivity reaction on tobacco leaves. Bacterial isolates passed from both hemolysis and hypersensitivity tests were then preserved by the lyophilization method for long-term storage of culture collection. Based on the hemolysis test, 68 out of 95 bacterial isolates (71.57%) were found to be positive (? or ?) reactions. The hypersensitive test showed that 22 of 27 negative hemolysis isolates did not trigger hypersensitivity reactions in tobacco leaves, therefore, they were preserved by lyophilization. The study indicated that a high number of bacterial isolates in the present collection, 68 positive hemolysis, and 5 hypersensitive, need to be re-evaluated due to their safety concerns. The present study highlights the importance of biosafety tests performed in an early stage before the to permanent collection of antagonist isolates.